2020
DOI: 10.3390/w12051299
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Water Security in Water-Scarce Cities: Applying the Integrated Urban Water Security Index (IUWSI) in Madaba, Jordan

Abstract: Water security is a major concern for water-scarce cities that face dynamic water challenges due to limited water supply, climate change and increasing water demand. Framing urban water security is challenging due to the complexity and uncertainties of the definitions and assessment frameworks concerning urban water security. Several studies have assessed water security by granting priority indicators equal weight without considering or adapting to the local conditions. This study develops a new urban water se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 67 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…For the study of WRCC, international scholars have mainly focused on water security [17][18][19], whereas Chinese scholars have focused on the concept and connotation of WRCC [20][21][22]. Scholars generally believe that WRCC covers the water resources system, the economic and social system, and the ecological system [18][19][20][21][22][23]. The WRCC is defined by four dimensions: water quantity, water quality, water area, and water flow [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the study of WRCC, international scholars have mainly focused on water security [17][18][19], whereas Chinese scholars have focused on the concept and connotation of WRCC [20][21][22]. Scholars generally believe that WRCC covers the water resources system, the economic and social system, and the ecological system [18][19][20][21][22][23]. The WRCC is defined by four dimensions: water quantity, water quality, water area, and water flow [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Water resources factors include the quantity and quality of water sources, the development and utilization of water resources, and the self-purification capacity of water bodies [8,29]. Economic factors include the level of economic development, productivity, and economic structure [18,30]. Social factors include population size and growth rate, labor force quality, urbanization rate, and the level and mode of social consumption [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…UWS in relation to population size and growth has been the focus of many studies from the 1990s (VĂśrĂśsmarty et al, 2000;Cook and Bakker, 2012). Most recent studies have demonstrated the development of numerous definitions and assessment frameworks for UWS over the past decade (Denton, 2002;Lundqvist et al, 2003;MacGregor, 2009;Demetriades and Esplen, 2010;Vorosmarty et al, 2010;Sullivan, 2011;Truelove, 2011;Aihara et al, 2015;Muller, 2016;Pangare, 2016;Romero-Lankao and Gnatz, 2016;Thompson, 2016;Harris et al, 2017;Hellberg, 2017;Allan et al, 2018;CastĂĄn Broto and Neves Alves, 2018;Shrestha et al, 2018;van Ginkel et al, 2018;Aboelnga et al, 2019Aboelnga et al, , 2020Sultana, 2020). It is proven that UWS is driven by a complex set of biophysical and social factors-which needs to be dealt with together, rather than independently.…”
Section: Urban Water Security Assessment So Farmentioning
confidence: 99%
“…In the context of SDGs 5 (Gender Equality) and 6 (Water and Sanitation), globally driven efforts and initiatives are being implemented to empower women, improve rural water accessibility, and reduce water‐related risks. Although researchers have increasingly developed different methods and tools over the past decade for assessing or measuring household water insecurity (Aboelnga et al, 2020; A. A. Brewis, Piperata, et al, 2020; Octavianti & Staddon, 2021; C. Schuster‐Wallace et al, 2019), such perspectives do not adequately explain and address the intersecting drivers of rural water inaccessibility, the feedback loops, and the ensuing consequences.…”
Section: Introductionmentioning
confidence: 99%